Penerapan Total Physical Response dalam pengajaran kosakata Human Emotion dalam Bahasa Inggris - Yulita, Delti; Neno, Hesni; Sulaiman, Eugelin; Aprianti, Iis (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Learning vocabulary is a crucial stage in English learning at early age because it could improve children communication skill. In order to teach vocabulary, teachers need to apply a fun and friendly method that could improve young learners’ vocabulary acquisition. Thus, this activity used Total Physical Response to teach students English vocabulary about human emotion. Human emotion is an adjective that often in daily life. Bu using TPR, the students were able to express their emotion in a proper way and use it in everyday life. The implementation of TPR showed that the students are more familiar with positive emotion rather that negative emotion. The students were more expressive in the learning process and it improves their vocabulary through imitating and repetition.